Control de dolor post-operatorio leve-moderado con una dosis de paracetamol intravenoiso comparando su eficacia con ketorolaco y metamizol en pacientes sometidos a procedimientos quirúrgicos en el hospital de los Valles. - Pullaguary A., Myriam C. (2014)
The pain post-operative, the present until date, It has been a theme of studies with a lot of importance clinic, because It through of its handling, we can give quality’s attention to patient and above all that the experience of the same It has not had consequence in your daily basis. In context our survey has by purpose it has known the efficacy of the intravenous-paracetamol in the pain’s control post-operative slight-moderate. In the present time is already considerate, as medical report of the basic drugs’ arsenal of the anesthesiologist, It had made use of in the trans-operative and post-operative immediate we have observed excellent results after than of its intravenous administration, and that in these last years was approved for the FDA to has been put in our hospitable environment Of the 50 patients that part way our survey, 25 received intravenous paracetamol and the other 25 had administered Metamizol-Ketorolac, 30 minutes before of the end of surgical procedure; 36% of the patients that received paracetamol did not demonstrate have pain and the same frequency for the group of pain slight without the necessity of analgesia’s rescue this was in the immediate post-operative in the UNITY of Care Post-Anesthetics So we have canned say that 1 g of intravenous paracetamol is effective in the acute pain’s control post-operative slight to moderate, with setting of use of opioid and rest of the security above all when the use of the nsaids are contraindicate